2020
DOI: 10.3390/mca25020021
|View full text |Cite
|
Sign up to set email alerts
|

The Strain Rates in the Brain, Brainstem, Dura, and Skull under Dynamic Loadings

Abstract: Knowing the precise material properties of intracranial head organs is crucial for studying the biomechanics of head injury. It has been shown that these biological tissues are significantly rate-dependent; hence, their material properties should be determined with respect to the range of deformation rate they experience. In this paper, a validated finite element human head model is used to investigate the biomechanics of the head in impact and blast, leading to traumatic brain injuries (TBI). We simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…1418 Hence, natural fibers have appeared as a potential replacement for the synthetic fibers and natural fibers based composites have already started to dominate in various industries. 1924…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1418 Hence, natural fibers have appeared as a potential replacement for the synthetic fibers and natural fibers based composites have already started to dominate in various industries. 1924…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Hence, natural fibers have appeared as a potential replacement for the synthetic fibers and natural fibers based composites have already started to dominate in various industries. [19][20][21][22][23][24] Kenaf, jute, sisal, flax, and hemp are the most commonly used natural fibers that are incorporated in the polymer matrix to tailor the mechanical properties. 19 Though these fibers are extracted from different plants, most of them possess a similar structure.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should also include a larger sample size, different age groups, and male players. In a different direction, researchers could explore the biomechanics of RHI using a finite element model of a human head as is done in impacts and blasts resulting in traumatic brain injuries [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, research on blast wave propagation inside of the combat helmets is based almost exclusively on data from numerical simulations [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Advances in medical diagnostic techniques such as magnetic resonance imaging (MRI) and computed tomography (CT) has facilitated the development of high-fidelity, anatomically accurate head models [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Progress in these fields stimulated the development of high-fidelity computational methods that helped identify mechanisms governing blast loading of the brain without a helmet. The finite element method (FEM) based numerical simulations demonstrated that in the early stages of the blast wave interaction with the head, the intracranial pressure is increased (compressive wave) at the coup (impact) side, which is accompanied by the development of the underpressure (tensile wave) on the counter-coup side [8,18,19,23,24]. This mechanism is universal and independent of the direction of the blast wave propagation, which was confirmed not only for the front impact but also for the blast waves directed at the head from the side, back, top, or the bottom [13,15,23].…”
Section: Introductionmentioning
confidence: 99%